IMPACT OF HOUSEHOLD WASTE DISPOSAL (Case study of Rawa Mas Indah Housing) - Magly Suphyan; Teuku Syahrul Ansari (Universitas Labuhanbatu, 2023)
Household waste or commonly referred to as garbage is waste generated from activities carried out daily in household life that do not include feces and specific waste. environmental regulations, regulations governing the environment, especially the management of household waste/waste, have been regulated by government regulation No. 81 of 2021 concerning the management of household waste and household-like waste, there are obstacles faced in waste management due to the low level of concern for waste from the household itself, the lack of garbage disposal sites, and less strict law enforcement against violators.Keywords: Household Waste, Pollution, Environment